FACTORS WHICH FORM COSTS IN CONSTRUCTION COMPANIES IN SURABAYA - Benediktus Derry Galista; David Sukardi Kodrat (SEAN Institute, 2023)
The goal is to recognize and examine the factors that shape costs in construction companies in Surabaya. The sample of this research used employees at construction companies in Surabaya. The sample group is equivalent to the full population, namely 103 respondents. Research variables used in the study are: Product Quality Improvement (x1); Increased Worker Productivity (x2); Reducing Unnecessary Costs (x3); Material Order Timeliness (x4); Material Delivery Timeliness (x5); Materials and Tools Inventory (x6); Rework; (x7) Company overhead (x8); Cost of Materials/Materials (x9); Project duration (x10); Performance optimization (x11); Ensure inventory and tool performance (x12); Company performance control (x13); Rework (x14); Reduced rework (x15); Management of the financial performance of the firm (x16); Improving the financial performance of the firm (x17); Material cost control (x18); Optimizing material costs (x19); Control the time working on the project (x20); and Optimizing project execution time (x21). The approach employed in this study is quantitative exploratory. The analytical approach utilized is exploratory factor analysis. The findings indicated that from 19 tested indicators, 6 factors formed the cost of construction companies. The six factors that shape costs in construction companies are: timeliness of orders, contractor costs, quality control, optimization of project work, on time delivery and inventory performance, and financial control.